2003
DOI: 10.1097/00002341-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vicryl Mesh in 200 Porous Orbital Implants

Abstract: Polyglactin 910 mesh is an excellent option as a wrapping material for porous orbital implants. It is simple to use, readily available, eliminates the need for donor tissue, does not require a second operative site, and it is less expensive than other currently available wrapping materials. We attribute our high success rate to our technique, which emphasizes proper placement of the implant within the Tenon space, suturing the extraocular muscles anterior to their normal anatomic sites, and meticulous closure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…16 The advantages of using vicryl mesh is the easy availability, it does not require donor tissue, is readily available, and no risk of the transmission of diseases, but it has a learning curve since the polyglactin 910 mesh-wrapped implant has different handling properties than a sclera-wrapped implant. 6 Our pilot study suggests that the use of bovine pericardium (Tutopatch s ) is a safe alternative to the other wrapping materials. Use of Tutopatch s decreases surgical time, as the autologous tissue does not need to be harvested.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…16 The advantages of using vicryl mesh is the easy availability, it does not require donor tissue, is readily available, and no risk of the transmission of diseases, but it has a learning curve since the polyglactin 910 mesh-wrapped implant has different handling properties than a sclera-wrapped implant. 6 Our pilot study suggests that the use of bovine pericardium (Tutopatch s ) is a safe alternative to the other wrapping materials. Use of Tutopatch s decreases surgical time, as the autologous tissue does not need to be harvested.…”
Section: Discussionmentioning
confidence: 87%
“…15 Vicryl mesh has also been used by many people with different levels of access. Jordan et al 6 reported an exposure rate of 2.1% within the first 2-3 months of surgery. Other authors have reported a high exposure rate in cases where vicryl mesh was used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Others include donor-processed pericardium and fascia lata. Popular synthetic wrapping materials are polyglactin-910 mesh, poly-tetrafluoroethylene sheet, 9 etc. The use of these synthetic wrapping materials significantly raises the cost of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic materials like Vicryl mesh and Dexon mesh eliminate the need for donor tissue or for a second incision as required with the use of autogenous tissue [19, 20]. They are inexpensive and carry little risk of infection.…”
Section: Discussionmentioning
confidence: 99%